Family Storytelling and Local Development - Romita, Tullio; Perri, Antonella (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2022)
As is known, for many years now, the economic and social development of urban areas, whether large or small, has been increasingly linked to the presence and level of diffusion of the tourist phenomenon. In such contexts, it is therefore extremely important for public governance to spend as fully as possible in creating situations that make one’s urban area capable of attracting an adequate shares of tourist flows (Semi, 2015). There is, however, an awareness that competition is now played out on a global and transmedia level (Jenkins, 2007), also through the design and provision of services and solutions that add value to the quality of local life (Nuvolati, 2007) and to the promised tourist experience (Augé, 1999). There is, moreover, an increasingly widespread belief that through place branding processes people's sense of belonging and territorial identity can be strengthened (Rizzi et al, 2018). The need to intervene is even more pressing in cases where urban areas have lost weight and relevance (Scattone, 2000), due to an economic and social structure that has not been able to adapt promptly to the changes undergone by society (Harvey, 2010). In fact, in these cases, we are faced with the problem of a reorganisation of public governance (Honh, Neuer, 2006) that also aims to recover the centrality and/or visibility of the place, as well as to mitigate the negative impacts that the 'crisis' has generated on the fabric of the city (unemployment, urban decay and abandonment, gentrification issues, etc.). In fact, in these cases, competition is even fiercer at the international level. For example, already more than thirty years ago, the Italian Fordist cities in crisis, in order to recover, had identified the tourism phenomenon as the sector in which to invest and, therefore, started urban regeneration processes that included the reconversion, reorganisation and reuse not only of abandoned urban areas, but also of some former industrial sites (for example, a well-known case is that of Genoa; Gazzola, 2006). Today, however, all this is no longer enough, and destinations wishing to compete in the national and international tourism market must also focus on building what is usually called place branding. That is, they must activate a mechanism of public governance capable of bringing out the emotional and experiential qualities of places, which can be summed up in a system of values with a clearly identifiable meaning. In this paper, we will deal with an element that we consider to be very special and not well known in the construction of place branding, which is what we call here "family storytelling". In particular, we intend to highlight the importance that "family storytelling" plays in the formation of place branding and the consequence in the local development of the destination. In this regard, we will make use of the case study of a particular and interesting tourist demand, which is that of those who travel to their family's places of origin, and the results of a qualitative survey involving a foreign community of Italian Americans.